A review of inspiratory muscle training. When and why does it work? - Faghy, M. (Human Science Research Centre, University of Derby, 2019)
The article reviews the following topics: - Respiratory Muscle Fatigue, the problem? - Inspiratory Muscle Training, the solution? - Inspiratory Muscle Training will not provide a uniform response.. - Functional Inspiratory Muscle Training.. - Clinical Application of Inspiratory Muscle Training..